2022
DOI: 10.1136/bmjopen-2021-052315
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ perspectives on equity of access to dialysis and kidney transplantation for rural people in Australia: a semistructured interview study

Abstract: ObjectivesPeople with chronic kidney disease requiring dialysis or kidney transplantation in rural areas have worse outcomes, including an increased risk of hospitalisation and mortality and encounter many barriers to accessing kidney replacement therapy. We aim to describe clinicians’ perspectives of equity of access to dialysis and kidney transplantation in rural areas.DesignQualitative study with semistructured interviews.Setting and participantsTwenty eight nephrologists, nurses and social workers from 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…In this study the proportion of ethnic groups was Burmese (139/168), Rakhine (8/168), Karen (7/168), Shan identifi ed the importance of fi nancial hardships though HDC were supported by government [10]. Socio-economic equity was emphasized in fi ndings from Indonesia study; higher frequency of hemodialysis use wes directly aff ected by higher family income, distance < 20 km, working in informal sector, benefi ciary of government subsidy, longer duration of hemodialysis, severe condition of illness, and living in urban area [11].…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…In this study the proportion of ethnic groups was Burmese (139/168), Rakhine (8/168), Karen (7/168), Shan identifi ed the importance of fi nancial hardships though HDC were supported by government [10]. Socio-economic equity was emphasized in fi ndings from Indonesia study; higher frequency of hemodialysis use wes directly aff ected by higher family income, distance < 20 km, working in informal sector, benefi ciary of government subsidy, longer duration of hemodialysis, severe condition of illness, and living in urban area [11].…”
Section: Resultsmentioning
confidence: 60%
“…The researchers from Australia found that geographical barriers were important in long term adherence [10]. Half of the patients required an hour travel time to HDC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many barriers impede Aboriginal and Torres Strait Islander people who live with dialysis from accessing waitlisting, including slow or delayed assessments and referrals, cultural bias, misinformation, and the difficulties of distance (Box). 4‐9 …”
mentioning
confidence: 99%
“…A phenomenological research method of qualitative research was adopted, and one-on-one interviews were conducted using a semi-structured interview method. As the most commonly used method for collecting qualitative research data, semi-structured interviews are relatively focused, do not deviate far from the topic, and can uncover a deep level of information [ 5 ]. An interview outline was developed before the interview, and the approval of the Ethics Committee was obtained.…”
mentioning
confidence: 99%